Diagnosis and isolation of Toxoplasma gondii in horses from Brazilian slaughterhouses - Fernanda Evers (Revista Brasileira de Parasitologia Veterinária, 2013)
This study aimed to investigate anti-Toxoplasma gondii antibodies and to isolate the parasite from the brains of horsesprocessed at slaughterhouses in Brazil. We collected brain and blood samples from 398 horses of various ages, from sixBrazilian states. Serum samples were evaluated by indirect fluorescent antibody test (IFAT cut-off titre ≥ 1:64), andbrains were submitted to mouse bioassay. Among the 398 horses, positivity for T. gondii was identified in 46 (11.6%)by IFAT and in 14 (3.5%) by mouse bioassay. In 12 of those 14 bioassays, mice were positive only by IFAT (cut-offtitre ≥ 1:16), T. gondii being isolated in the remaining two. Using polymerase chain reaction-restriction fragment lengthpolymorphism (PCR-RFLP) analysis of 18S rDNA to differentiate among T. gondii, Neospora caninum, and Sarcocystisneurona, we found that two of the 14 brains were positive for T. gondii only. For genotyping of the two isolates and thePCR-positive brain, we performed PCR-RFLP based on 13 markers, and SAG2 all samples were Toxoplasma gondiitype I. Collectively, IFAT of horse sera and mouse bioassay identified positivity in 60 (15%) of the samples. Our resultsshow that some horses sent to slaughter in Brazil have been exposed to T. gondii.